BEETGE, GH Inventory of documents - BEETGE, GH (ARCA, 2018)
Private papers of G.H. Beetge, Deputy Chairman of the Herstigte National Party [HNP]. He fought several elections as candidate for the HNP without success.
COVERAGE 1941-1984; 4 Files; 0,40 Metres.
Keywords: BEETGE, GH; Inventories; Politicians; National Party